Strengthening Tax Compliance through Good Public Governance - Sari, Imelda; Hasan, Nida Nadya (Research of Accounting and Governance, 2026)
This study examines the effects of taxpayer knowledge and changes in tax regulations on individual taxpayer compliance, with good public governance as a mediating variable. Despite the widespread implementation of the self-assessment system, taxpayer compliance remains a persistent challenge, particularly amid frequent regulatory changes and varying governance quality. Using a quantitative approach, this study involved 100 individual taxpayers registered at the Kemayoran Pratama Tax Office in Jakarta, selected through incidental sampling. Data were collected via questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS 4.1.9. The results indicate that taxpayer knowledge has a positive and significant effect on compliance, while changes in tax regulations have a significant negative effect. However, both taxpayer knowledge and regulatory changes positively influence good public governance, which in turn significantly enhances taxpayer compliance. Furthermore, good public governance mediates the relationship between taxpayer knowledge and compliance, as well as between regulatory changes and compliance, mitigating the adverse effects of regulatory complexity. These findings contribute to tax compliance literature by highlighting the critical mediating role of governance quality. From a policy perspective, strengthening transparent, consistent, and well-communicated governance frameworks is essential to improving voluntary tax compliance and supporting sustainable revenue mobilization.